HAMBATAN KOMUNIKASI ANTAR BUDAYA MAHASISWA NTT DI YOGYAKARTA - Aleksis Febrian Go; Irene Santika Vidiadari (Universitas Muhammadiyah Jember, 2020)
This study discuss the barriers to intercultural communication experienced by students from East Nusa Tenggara (Nusa Tenggara Timur or NTT) while studying in Yogyakarta. This research starts from the condition of Yogyakarta as one of the destination for students from all over Indonesia to continue their educations, especially students from NTT. This research use qualitative descriptive as a method, data collected by interviewing the students from NTT and also collecting data from the media. The results indicate that the differences of language, habits, and perceptions made the barriers to intercultural communication for NTT students. In addition, the stereotypes attached to NTT students such as troublemaker, came from underdeveloped area, and easily commit to criminal acts are the sources of gaps between NTT students and other people around them